Traffic Equilibrium Problems with Cross-Boundary Traffic: A Tradable Credit Approach. (14th June 2022) - Liang, Qingnan; Sumalee, Agachai; Zhong, Renxin
Abstract : This study studies the tradable credit scheme design problem considering a mixture of local traffic and cross-boundary traffic. The local traffic refers to the travel demand generated by local residents with O-D pairs inside the network, while the cross-boundary traffic is the traffic with either origin or destination or both be outside the network. As the local authority aims to maximize its local social welfare, it determines the quantity of cross-boundary trips by evaluating the revenue of the cross-boundary traffic. Two credit charging schemes are investigated, i.e., a spatially differentiated credit scheme and an anonymous tradable credit scheme. In the first scheme, due to the different charging prices and the selfishness of the local authority, the travel credits are freely tradable within the local travellers only. The cross-boundary travellers have to buy travel credits from the local authority. In the second scheme, the tradable credit scheme is anonymous. The local authority determines the link-specific number of credits to be charged for using that link, while the travel credits are distributed to local travellers only but are allowed for free trading among both local and cross-boundary travellers. Two standard multi-class traffic equilibrium problems are established with side constraints and a credit restriction constraint. The equilibrium link flow patterns under these credit schemes are then demonstrated with local elastic demand. In both tradable credit schemes, the credit price in the trading market is unique under the equilibrium condition.